A MULTIVARIATE TWIN STUDY OF TRAIT MINDFULNESS, DEPRESSIVE SYMPTOMS, AND ANXIETY SENSITIVITY. Issue 4 (30th January 2015) - Waszczuk, Monika A.; Zavos, Helena M. S.; Antonova, Elena; Haworth, Claire M.; Plomin, Robert; Eley, Thalia C.
Abstract : Background: Mindfulness‐based therapies have been shown to be effective in treating depression and reducing cognitive biases. Anxiety sensitivity is one cognitive bias that may play a role in the association between mindfulness and depressive symptoms. It refers to an enhanced sensitivity toward symptoms of anxiety, with a belief that these are harmful. Currently, little is known about the mechanisms underpinning the association between mindfulness, depression, and anxiety sensitivity. The aim of this study was to examine the role of genetic and environmental factors in trait mindfulness, and its genetic and environmental overlap with depressive symptoms and anxiety sensitivity. Methods: Over 2, 100 16‐year‐old twins from a population‐based study rated their mindfulness, depressive symptoms, and anxiety sensitivity. Results: Twin modeling analyses revealed that mindfulness is 32% heritable and 66% due to nonshared environmental factors, with no significant influence of shared environment. Genetic influences explained over half of the moderate phenotypic associations between low mindfulness, depressive symptoms, and anxiety sensitivity. About two‐thirds of genetic influences and almost all nonshared environmental influences on mindfulness were independent of depression and anxiety sensitivity. Conclusions: This is the first study to show that both genes and environment play an important role in the etiology of mindfulness in adolescence. Future research should identify the specific environmental factors that influence trait mindfulness during development to inform targeted treatment and resilience interventions. Shared genetic liability underpinning the co‐occurrence of low mindfulness, depression, and anxiety sensitivity suggests that the biological pathways shared between these traits should also be examined.